Some comparative studies of the fauna in soils developed under natural forest, pine and bluegum - Watts, John Christopher David (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1952)
[From Introduction] It has been said that, "If a nation saves its trees, the trees will save the nation." The truth of this assertion is apparent in many parts of the world today. In South Africa, fires and demands in the past for timber have led to extensive depletion of the Natural Forests. In many cases, natural revegetation has been slow to develop and deterioration of the soil has resulted. The desire to replace the tree cover and at the same time to meet an increasing internal demand for timber, has led to widespread planting of Pine and Bluegum. It is probable that more trees have now been planted than were destroyed in the past. The silviculturist however, who develops a pure stand on land which previously supported the mixed stand, should anticipate a change in soil properties as a natural accompaniment of such an undertaking. The nature of this change is the primum mobile of the present comparative study. The forest soils studied were taken in the Cape Province in the following areas:- Grahamstown; Amatola Mountains, District Alice; Witte-els-Bosch, District Humansdorp, during the course of a year. The physical and chemical properties, and the faunal composition of the soil samples were examined in relation to the different tree covers. Because of the necessity of taking large numbers of samples and thorough examination of these to arrive at a definite conclusion, the work is necessarily incomplete. It is felt however that the results obtained justify a further study of this aspect of soil biology.
Keywords: Soil science; Forest ecology; Soil animals